Purinergic Enhancement of Anti-Leishmanial Effector Functions of Neutrophil Granulocytes - Möller, Sonja; Laskay, Tamás (Frontiers in Immunology, 2021)
Although macrophages are considered for host cells for the multiplication of Leishmania, recent studies indicate the important role of neutrophil granulocytes as host cells for these intracellular parasites. Neutrophils have been shown to be massively and rapidly recruited to the site of Leishmania infection where they represent the first cells to encounter the parasites. Exposure to ATP and UTP have been shown to enhance anti-Leishmania activity of macrophages and intralesional injection of UTP led to strongly reduced parasite load in vivo. Since the in vivo anti-leishmanial effect of extracellular UTP correlated with enhanced neutrophil recruitment and enhanced ROS production at the site of Leishmania infection we hypothesized that exposure to extracellular nucleotides can directly enhance the killing of Leishmania by neutrophils. Since purinergic signaling is an essential mechanism of neutrophil activation the aim of the present study was to assess whether purinergic exposure results in the activation of anti-leishmanial neutrophil functions and, therefore, represent an essential component of enhanced anti-leishmanial defense in leishmaniasis. We could show that exposure to ATP and UTP led to activation and enhanced CD11b expression of primary human neutrophils in vitro. Leishmania-induced ROS production was strongly enhanced by extracellular ATP and UTP. Importantly, exposure to ATP and UTP resulted in enhanced killing of Leishmania donovani by neutrophils. In addition, ATP strongly enhanced the secretion of IL-8 and IL-1 beta by Leishmania-exposed neutrophils. Our results suggest that signaling via the P2 receptor and phosphorylation of Erk1/2, Akt and p38 are involved in the purinergic enhancement of anti-leishmanial functions of neutrophils.